The beginnings of electron microscopy. - Hawkes, P. W.; Hytch, Martin (Advances in imaging and electron physics ;, 2021)
"The Beginnings of Electron Microscopy - Part 1, Volume 220 in the Advances in Imaging and Electron Physics series highlights new advances in the field, with this new volume presenting interesting chapters on Electron-optical Research at the AEG Forschungs-Institut 1928-1940, On the History of Scanning Electron Microscopy, of the Electron Microprobe, and of Early Contributions to Transmission Electron Microscopy, Random Recollections of the Early Days, Early History of Electron Microscopy in Czechoslovakia, Personal Reminiscences of Early Days in Electron, Megavolt Electron Microscopy, Cryo-Electron Microscopy and Ultramicrotomy: Reminiscences and Reflections, and much more."--Publisher's web page, viewed October 26, 2021